Examining reciprocal associations between parent depressive symptoms and child internalizing symptoms on subsequent psychiatric disorders: An adoption study. Issue 12 (29th June 2021) - Cioffi, Camille C.; Leve, Leslie D.; Natsuaki, Misaki N.; Shaw, Daniel S.; Reiss, David; Ganiban, Jody M.; Neiderhiser, Jenae M.
Abstract: Introduction: The dynamic interplay between parent depressive symptoms and child internalizing behavior over time is not well understood. Methods: We used data from a prospective parent‐offspring adoption design ( N = 561) to examine associations between adoptive parent depressive symptoms and child internalizing behavior when children were ages 18 months, 27 months, 4.5 years, and 6 years, and subsequent child psychiatric disorder symptoms when children were between the ages of 6–8 years. Models also accounted for the contributions of birth parent psychopathology, birth mother depressive symptoms during pregnancy, and infant negative emotionality. Bidirectional associations between adoptive parent depressive symptoms and child internalizing behavior were examined using a random‐intercept cross‐lagged panel model. Results: There was evidence for associations between child internalizing behavior and adoptive parent depressive symptoms over time, with mothers' depressive symptoms being a more salient risk factor for child internalizing behavior than fathers'. We found one significant cross‐lagged association from adoptive mother depressive symptoms at child age 18 months to child internalizing behavior at age 27 months. Infant negative emotionality (i.e., emotional liability) at age 9 months predicted both child internalizing behavior and adoptive parent depressive symptoms. Conclusion: Results suggest that postnatal maternal depressive symptoms confer specific risks for child internalizing behaviors in toddlerhood and childhood and depressive symptoms in childhood.